The Effect of Preoperative Naproxen Sodium on the Efficacy of Inferior Alveolar Nerve Block in Patients with Symptomatic Irreversible Pulpitis - Hina Khan; Abdur Rehman; Syed Abrar Ali; Fariha Irfan; Hira Akhtar; Mohammad Hammad (JLUMHS, 2022)
OBJECTIVE: To inspect the effects of naproxen sodium pre-operatively on the potency of Inferior alveolar nerve block in patients suffering from symptomatic irreversible pulpitis. METHODOLOGY: A cross-sectional study was conducted at Operative Department, Hamdard University Dental Hospital Karachi, from July 2018 to February 2019 using a non-probability consecutive sampling technique, including patients between 18-45 years of age. One hundred patients with symptomatic irreversible pulpitis in the posterior teeth of the mandible were randomly given 550 mg naproxen sodium or similar placebo capsules 60 minutes before the delivery of a conventional inferior alveolar nerve block. Patients having allergies, contraindications to naproxen sodium, pregnancy, lactating mothers, not giving consent, patients experiencing only mild pain (verified with Visua l Analog scale) or taking pain medication in the last 6 hours were excluded. Fifteen minutes after the inferior alveolar nerve block delivery, sufficient lip numbness was confirmed, and endodontic therapy was commenced. Success determined if the subjects remained pain-free or showed mild pain (≤54mm on a 170mm Visual analog scale) on access or instrumentation. SPSS version 22 was utilized for data analysis. RESULTS: The success of the inferior alveolar nerve block demonstrated by the placebo group was 40%, and the experimental group was remarkably 98%. A substantial significant difference was evident between the two research groups. CONCLUSION: Variations in the two groups support that a significant rise in the success rate of the inferior alveolar nerve block was observed in subjects who consumed a pre-operative dose of 550 mg naproxen sodium with symptomatic irreversible pulpitis.